The Role of Digital Services in Improving Public Services Correspondence for the Medan Balitbang Mayor Office during the Covid-19 Pandemic - Rahmawati Harahap (Penerbit Jurnal Indonesia, 2022)
In order to maximize public services, the Medan Mayor Balitabang office can create an online correspondence service system which is an alternative form of improving existing services. Increasing the standard of public services will be one of the efforts to prevent the Covid-19 virus. The method used in this research is qualitative and the type of this research is descriptive. The results show that the role of digital services in improving public services is a service program through a website that can make it easier for people to make licensing letters without having to go back to the office but just at home, people can take care of permits through the website.